Making the Connection (LEARNing Landscapes, 2007)
In "Making the Connection", I discuss, from a secondary high school student perspec- tive, the do’s and don’ts of how to engage students in the classroom. From the little details to the larger general concepts, this article outlines some ideas that could facilitate learning, and improve the classroom environment for both students and teachers.
Keywords: student engagement; classroom environment; secondary school